2020
DOI: 10.1364/oe.378270
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between two distinct nonlinear effects by polarization-resolved Z-scan measurements

Abstract: We investigated how the Z-scan technique can be explored to distinguish two types of nonlinear refractive effects by employing two distinct laser polarizations. It is possible that pure electronic, molecular orientation and thermal nonlinear effects may occur simultaneously during light-matter interaction. We found a way to discriminate and quantify two distinct nonlinear processes from Z-scan signals measured with linear and circular polarizations. This paper provides analytical equations for nonlinear refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…In a study regarding CS 2 , Reichert et al discussed how the electronic nonlinear response has a strong polarization dependence, with a more pronounced effect for linearly polarized light. 25 This result is supported by Melhado et al, 26 which showed that electronic and orientational nonlinear effects are polarization-dependent, while thermal nonlinearities are not, an indication that the observed nonlinearities in our experiments are most likely of thermal origin. In a recent work, Bautista et al 20 discussed in detail the physical mechanisms responsible for SSPM of Gaussian beams interacting with liquid suspensions of 2D materials when CW or ML high repetition-rate lasers are employed.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a study regarding CS 2 , Reichert et al discussed how the electronic nonlinear response has a strong polarization dependence, with a more pronounced effect for linearly polarized light. 25 This result is supported by Melhado et al, 26 which showed that electronic and orientational nonlinear effects are polarization-dependent, while thermal nonlinearities are not, an indication that the observed nonlinearities in our experiments are most likely of thermal origin. In a recent work, Bautista et al 20 discussed in detail the physical mechanisms responsible for SSPM of Gaussian beams interacting with liquid suspensions of 2D materials when CW or ML high repetition-rate lasers are employed.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…In a study regarding CS 2 , Reichert et al discussed how the electronic nonlinear response has a strong polarization dependence, with a more pronounced effect for linearly polarized light . This result is supported by Melhado et al, which showed that electronic and orientational nonlinear effects are polarization-dependent, while thermal nonlinearities are not, an indication that the observed nonlinearities in our experiments are most likely of thermal origin.…”
Section: Resultssupporting
confidence: 84%
“…Actually, we verified that in our experimental setup, the excitation beam profile could not be described as a fundamental Gaussian beam; moreover, the thin sample approximation was not fully verified. Therefore, we used the known value of the CS2 sample nonlinear refractive index for hundred-femtosecond pulses, i.e., γref = 2 × 10 −6 cm 2 /GW [23,[25][26][27], as a reference value to calibrate our system and to obtain the Kerr nonlinearity of other samples, using the method described in [28], essentially exploiting the linear dependence of the Z-scan peak-valley amplitude ΔTpv on the nonlinear refractive index for small nonlinearities. Here, the peak-valley amplitude of the CS2 reference sample was ∆𝑇 = 13%, and thus, given the measured value ∆𝑇 of an unknown sample in the same excitation conditions, the associated refractive index is given by As evidenced by an attempt to fit the data with the commonly used simple theoretical model [20], assuming a TEM 00 Gaussian beam, thin sample and small nonlinearities, the experimental traces deviated substantially from the model.…”
Section: Methodsmentioning
confidence: 99%
“…Polarization z-scan allows for a comprehensive analysis of the material's anisotropic properties, revealing how nonlinear optical behavior changes with different polarizations [35][36][37][38][39][40][41]. In this report, we used the polarization z-scan technique to probe the interparticle plasmon coupling within AuNP dimers as well as establish their presence and structural characteristics.…”
Section: Introductionmentioning
confidence: 99%